Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1399-0004.2011.01715.x
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon‐based high‐throughput pooled sequencing identifies mutations in CYP7B1 and SPG7 in sporadic spastic paraplegia patients

Abstract: Hereditary spastic paraplegia (HSP) is a neurodegenerative disorder defined clinically by progressive lower limb spasticity and weakness. HSP is a genetically highly heterogeneous condition with at least 46 gene loci identified so far, involving X-linked, autosomal recessive (AR) and autosomal dominant inheritance. For correct diagnosis, molecular testing is essential because clinical parameters by themselves are not reliable to differentiate HSP forms. The purpose of this study was to establish amplicon-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 34 publications
(68 reference statements)
3
31
0
Order By: Relevance
“…The improvement of nucleotide sequencing has recently demonstrated the possibility of accelerating and improving cost-effectiveness of genetic diagnosis using an array-based amplification strategy after generation of amplicon libraries of all currently known HSP genes followed by a pooled next-generation sequencing (NGS) (Chase, 2014;Novarino et al, 2014;Schlipf et al, 2011). Besides, modern methodologies of re-sequencing have been reported as well as a gene chip screening (Luo et al, 2013).…”
Section: Diagnosismentioning
confidence: 99%
“…The improvement of nucleotide sequencing has recently demonstrated the possibility of accelerating and improving cost-effectiveness of genetic diagnosis using an array-based amplification strategy after generation of amplicon libraries of all currently known HSP genes followed by a pooled next-generation sequencing (NGS) (Chase, 2014;Novarino et al, 2014;Schlipf et al, 2011). Besides, modern methodologies of re-sequencing have been reported as well as a gene chip screening (Luo et al, 2013).…”
Section: Diagnosismentioning
confidence: 99%
“…The p.His448Profs * 12 mutation is predicted to result in a premature stop codon. Previous reports (7,(9)(10)(11)(12)(13)(14)(15) have revealed that missense and nonsense mutations located closer to the C-terminal of paraplegin than the p.His448Profs * 12 mutation can cause disease ( Figure D). Recently, genotype-phenotype correlations were identified for SPG7: an association between cerebellar ataxia and SPG7 null alleles leading to an absence of protein products or severely truncated protein products and an association between optic nerve atrophy and a missense mutation in exon 10 (pArg470Gln) (9).…”
Section: Discussionmentioning
confidence: 99%
“…NGS facilitates researchers with the required capacity to analyze large panels of genes for suspected genetic diseases. These diseases vary from single gene disorders such as Neurofibromatosis Type 1 (NF1), Marfan syndrome (MFS), and spastic paraplegia [50,53,54] to diseases caused by a group of related genes such as hypertrophic cardiomyopathy and congenital disorders of glycosylation (CDG) [19,20,51]. NGS has also been applied to multi-gene disorders including X-linked intellectual disability (XLID) [18] and retinitis pigmentosa [52], as well as defined disorders without identified genetic causes [55][56][57] (Table 4).…”
Section: Mendelian and Rare Diseasesmentioning
confidence: 99%